KEMAMPUAN MENGAJAR MAHASISWA PPLK MENURUT PERSEPSI GURU PAMONG PADA PROGRAM KEAHLIAN TEKNIK BANGUNAN SMK DI KOTA PADANG TAHUN AJARAN 2016/ 2017 - Aldo Sepra Johannes; Juniman Silalahi; Risma Apdeni (CIVED, 2018)
Abstract— The background of this research is various problems found in the implementation of PPLK, which are related to the teaching ability of PPLK students. The purpose of this study is to reveal the teaching ability of PPLK students according to the perceptions of supervisor teachersin Building Engineering Department of SMK in Padang City in academic year 2016/2017. The type of this research is quantitative descriptive research. The population is all supervisor teachers in Building Engineering Department of SMK in Padang City amounting 28 teachers. The sample was taken by using total sampling technique. The type of data used is primary and secondary data. Primary data were obtained through questionnaire about perceptions of supervisor teachers on the teaching ability of PPLK students that distributed to the respondents. Secondary data was the number of supervisor teachers obtained from the Head of Building Engineering Department. Data analysis techniques used are: (1) Data verification, (2) Data classification and tabulation, (3) Data processing by calculating frequency and mean value. The results showed that the teaching ability of PPLK students according to the perceptions of supervisor teacherin Building Engineering Department of SMK in Padang City is in fair category. Viewed per indicator, the perceptions of supervisor teachers towards 3 indicators (pedagogical, personality, and professional competency) are in fair category, while for social competencyis in good category.Keywords: Perception, Supervisor Teacher, Teaching Ability